2014
DOI: 10.1111/cag.12104
|View full text |Cite
|
Sign up to set email alerts
|

A more national representation of place in Canadian daily newspapers

Abstract: In their design and content, North American daily newspapers construct a complex representation of the locality they serve and its place in the world. That construct involves the quality and quantity of local news, relative to news in other geographic categories, and how stories from each category are displayed in the newspaper's pages. This article describes a content analysis that quantified and compared the representations of locality and place in the print versions of two Canadian metropolitan daily newspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Another study pointed to a significant reduction in the amount and prominence of local news in the Toronto Star and Ottawa Citizen newspapers after 1970. Growing concerns about national unity likely accounted for some of the increased emphasis on national coverage, but chain ownership that emphasized cost-effective production and the sharing of national stories across the group was also cited as a explanation, particularly in the case of the Ottawa Citizen, where the decline in local reporting was the most notable (Buchanan, 2014).…”
Section: The Canadian Contextmentioning
confidence: 99%
“…Another study pointed to a significant reduction in the amount and prominence of local news in the Toronto Star and Ottawa Citizen newspapers after 1970. Growing concerns about national unity likely accounted for some of the increased emphasis on national coverage, but chain ownership that emphasized cost-effective production and the sharing of national stories across the group was also cited as a explanation, particularly in the case of the Ottawa Citizen, where the decline in local reporting was the most notable (Buchanan, 2014).…”
Section: The Canadian Contextmentioning
confidence: 99%
“…question in the 'what, where, who, why, how and when?' template of journalistic investigation is increasingly disregarded (see, for example, Buchanan, 2009;Funk, 2012), collaborating with Indigenous sources can reverse this by informing journalists about the underlying character of places. From Bourdieu, who connects his theoretical mainstay of habitus (see Mason, et al, 2016) with the notion of place, stating that habitus 'implies a "sense of one's place" and a "sense of the place of others"' (Bourdieu, 1989, p. 19) within a field of endeavour, Thomson, et al (2015, p. 141) suggest two potential benefits.…”
Section: Isn't That Recognising Its Heritage? -'Wexford'mentioning
confidence: 99%
“…Buchanan found that some Canadian newspapers have offered less local coverage that represents their cities distinctively, instead providing readers "more national representations of place." 33 This focus on the national perspective-as opposed to a recognizably local representation of news and issues-could reflect a variety of factors, Buchanan argues, including the rise of television and digital news sources that have supplanted newspapers' local, unifying role. City magazines could perhaps become a reinvigorated source for that lost local representation, providing readers a cohesive look at their locales.…”
Section: Representations Of People and Places In City Magazinesmentioning
confidence: 99%